2020
DOI: 10.1002/mc.23174
|View full text |Cite
|
Sign up to set email alerts
|

PYCR1 knockdown inhibits the proliferation, migration, and invasion by affecting JAK/STAT signaling pathway in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD), as a form of non‐small cell lung cancer (NSCLC), is the most frequently diagnosed lung cancer worldwide. To date, a few biomarkers have been reported to provide valuable information in guiding LUAD treatment. The aim of our study was to explore the functional role of pyrroline‐5‐carboxylate reductase 1 (PYCR1) in LUAD. Based on Oncomine database, we found that PYCR1 was highly expressed in LUAD tissues. We also confirmed an abnormal increase of PYCR1 expression in LUAD cell lines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
5
26
0
Order By: Relevance
“…Additionally, another reports demonstrated that PYCR1 interference inhibited cell proliferation and enhanced cell apoptosis in hepatocellular carcinoma by repressing JNK/IRS1 pathway (Zhuang et al, 2019). In accord with the study of Yan et al (2019) and Gao et al (2020), our results also showed that PYCR1 could activate JAK/STAT signaling in the BCa cells. Therefore, we are highly convinced that the overexpression of RAC3 activated JAK/STAT signaling through PYCR1 axis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, another reports demonstrated that PYCR1 interference inhibited cell proliferation and enhanced cell apoptosis in hepatocellular carcinoma by repressing JNK/IRS1 pathway (Zhuang et al, 2019). In accord with the study of Yan et al (2019) and Gao et al (2020), our results also showed that PYCR1 could activate JAK/STAT signaling in the BCa cells. Therefore, we are highly convinced that the overexpression of RAC3 activated JAK/STAT signaling through PYCR1 axis.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, recent studies have also reported that PYCR1 is up-regulated in human cancers, and thus promote the progression of cancers including non-small-cell lung cancer (Wang et al, 2019), prostate cancer (Zeng et al, 2017), and hepatocellular cancer (Zhuang et al, 2019), among others. Moreover, Yan et al (2019) and Gao et al (2020) demonstrated that the knockdown of PYCR1 inhibits the activation of JAK/STAT signaling in lung adenocarcinoma and colorectal cancers, respectively. Additionally, another reports demonstrated that PYCR1 interference inhibited cell proliferation and enhanced cell apoptosis in hepatocellular carcinoma by repressing JNK/IRS1 pathway (Zhuang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pinch-1, a cell-extracellular adhesion protein, promotes proline biosynthesis by increasing the expression of P5CS (Cui et al 2021 ). Interestingly, SIRT3 regulates proline synthesis by deacetylation of PYCR1 enzyme protein and increasing proline synthesis (Chen et al 2019 ), and knockdown of PYCR1 in lung adenocarcinoma inhibits the proliferation and invasion by modulating JAK/STAT (Gao et al 2020 ). Inhibitors of HDAC induce PRODH transcription and anti-apoptotic autophagy in triple negative breast cancer (Fang et al 2019b ).…”
Section: Proline Metabolism and Cancermentioning
confidence: 99%
“…Other evidence came from reports showing that overexpressed PYCR1 was associated with poor prognosis [6]. The knockout of PYCR1 is sufficient to impair the in vivo proliferation in ccRCC cancer cells that can be negated by proline addition [5].…”
Section: Proline Starvationmentioning
confidence: 99%